Small-scale online simulations in guided-wave photonics - Hammer, Manfred (Integrated Optics: Devices, Materials, and Technologies XXVI)
Online solvers for a series of standard 1-D or 2-D problems in integrated optics will be discussed. Implemented on the basis of HTML/JavaScript/SVG with core routines compiled from well tested C++-sources, the quasi-analytical algorithms require a computational load that can be handled easily even by current mobile devices. So far the series covers the 1-D guided modes of dielectric multilayer slab waveguides and the oblique plane wave reflection from these, the modes of rectangular channel waveguides (in an approximation of effective indices), bend modes of curved multilayer slabs, whispering-gallery resonances (“Quasi-Normal-Modes”) supported by circular dielectric cavities, the hybrid modes of circular multi-step-index optical fibers, bound and leaky modes of 1-D complex multilayers, including plasmonic surface modes, and, with restrictions, quite general rectangular scattering problems in 2-D.
Keywords: tet_topic_waveguide

The “black box” of social commerce platforms-a closer look at users’ activities - Meydani, Elnaz; Düsing, Christoph; Fedrau, Annamaria; Trier, Matthias

Wie die Queen: Die deutsch-jüdische Geschichte einer sehr britischen Schriftstellerin - Ribbat, Christoph

Quasiparticle energies and optical response of RbTiOPO4 and KTiOAsO4 - Neufeld, Sergej; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
Many-body perturbation theory based on density-functional theory calculations is used to determine the quasiparticle band structures and the dielectric functions of the isomorphic ferroelectrics rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenide (KTiOAsO4). Self-energy corrections of more than 2 eV are found to widen the transport band gaps of both materials considerably to 5.3 and 5.2 eV, respectively. At the same time, both materials are characterized by strong exciton binding energies of 1.4 and 1.5 eV, respectively. The solution of the Bethe-Salpeter equation based on the quasiparticle energies results in onsets of the optical absorption within the range of the measured data.

Clean and Hydrogen‐Adsorbed AlInP(001) Surfaces: Structures and Electronic Properties - Glahn, Luis Joel; Ruiz Alvarado, Isaac Azahel; Neufeld, Sergej; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Ostheimer, David; Shekarabi, Sahar; Romanyuk, Oleksandr; Moritz, Dominik Christian; Hofmann, Jan Philipp; Jaegermann, Wolfram; Hannappel, Thomas; et al. (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Water/InP(001) from Density Functional Theory - Ruiz Alvarado, Isaac Azahel; Schmidt, Wolf Gero (ACS Omega)
Keywords: General Chemical Engineering; General Chemistry

P-Terminated InP (001) Surfaces: Surface Band Bending and Reactivity to Water - Moritz, Dominik Christian; Ruiz Alvarado, Isaac Azahel; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Frieß, Tilo; Runge, Erich; Hofmann, Jan P.; Hannappel, Thomas; Schmidt, Wolf Gero; Jaegermann, Wolfram (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Reconstructions of the As-Terminated GaAs(001) Surface Exposed to Atomic Hydrogen - Karmo, Marsel; Ruiz Alvarado, Isaac Azahel; Schmidt, Wolf Gero; Runge, Erich (ACS Omega)
Keywords: General Chemical Engineering; General Chemistry

Programmierung und Computersimulationen - Schindlmayr, Arno (Kompetent Prüfungen gestalten: 60 Prüfungsformate für die Hochschullehre)
Dieses Format eignet sich, um zu prüfen, inwieweit Studierende Computersimulationen und eigene kleine Programme zur Lösung typischer Probleme ihres Fachs nutzen können. Wie bei Klausuren erfolgt die Bearbeitung in begrenzter Zeit und unter Aufsicht, wird aber am Computer durchgeführt und beinhaltet neben der Programmierung auch vor- und nachbereitende Aufgaben im Kontext der fachlichen Anwendung.

Direct Measurement of Higher-Order Nonlinear Polarization Squeezing - Prasannan, Nidhin; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Protonation-induced charge transfer and polaron formation in organic semiconductors doped by Lewis acids - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (RSC Advances)
Lewis-acid doping of organic semiconductors (OSCs) opens up new ways of p-type doping and has recently become of significant interest.
Keywords: General Chemical Engineering; General Chemistry

Microscopic Study of Molecular Double Doping - Bathe, Thomas; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry A)
Keywords: Physical and Theoretical Chemistry

The Impact of Product Differentiation on Retail Bundling in a Vertical Market - Endres-Fröhlich, Angelika Elfriede; Hehenkamp, Burkhard; Heinzel, Joachim
We study the effects of product differentiation on the bundling incentives of a two-product retailer. Two monopolistic manufacturers each produce a differentiated good. One sells it to both retailers, while the other only supplies a single retailer. Retailers compete in prices. Retail bundling is profitable when the goods are close substitutes. Only then is competition so intense that the retailer uses bundling to relax competition both within and across product markets, despite an aggravation of the double marginalization problem. Our asymmetric market structure arises endogenously for the case of close substitutes. In this case, bundling reduces social welfare.
Keywords: Retail bundling; upstream market power; double marginalization; product differentiation

Modellierung des Stofftransportes in einer geneigten Kolonne mit dem Ansatz der hydrodynamischen Analogien - Ehlert, Thomas; Mamedov, Tural; Schubert, Markus; Kenig, Eugeny Y.

Electrochemical performance of KTiOAsO_4 (KTA) in potassium-ion batteries from density-functional theory - Bocchini, Adriana; Gerstmann, Uwe; Bartley, Tim; Steinrück, Hans-Georg; Henkel, Gerald; Schmidt, Wolf Gero (Phys. Rev. Materials)

Oxygen vacancies in KTiOPO_4: Optical absorption from hybrid DFT - Bocchini, Adriana; Gerstmann, Uwe; Schmidt, Wolf Gero (Phys. Rev. B)

Experimental Demonstration of a 2.2kW Active-Clamp Converter for High-Current Wide-Voltage-Transfer Ratio Applications - Rehlaender, Philipp; Korthauer, Bastian; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Phase-Shift Modulation for Flying-Capacitor DC-DC Converters - Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Development of a Hybrid Modeling Methodology for Oscillating Systems with Friction - Wohlleben, Meike Claudia; Bender, Amelie; Peitz, Sebastian; Sextro, Walter (Machine Learning, Optimization, and Data Science)

Analysis of the Segregation Phenomena of Wood Fiber Reinforced Plastics - Moritzer, Elmar; Flachmann, Felix; Richters, Maximilian; Neugebauer, Marcel (Journal of Composites Science)
Wood–plastic composites (WPC) are enjoying a steady increase in popularity. In addition to the extrusion of decking boards, the material is also used increasingly in injection molding. Depending on the formulation, geometry and process parameters, WPC tends to exhibit irregular filling behavior, similar to the processing of thermosets. In this work, the influence of matrix material and wood fiber content on the flow, mold filling and segregation behavior of WPC is analyzed. For this purpose, investigations were carried out on a flow spiral and a sheet cavity. WPC based on thermoplastic polyurethane (TPU) achieves significantly higher flow path lengths at a wood mass content of 30% than polypropylene (PP)-based WPC. The opposite behavior occurs at higher wood contents due to the different shear thinning behavior. Slightly decreased wood contents could be observed at the beginning of the flow path and greatly increased wood contents at the end of the flow path, compared to the starting material. When using the plate cavity, flow anomalies in the form of free jets occur as a function of the wood content, with TPU exhibiting the more critical behavior. The flow front is frayed, but in contrast to the flow spiral, no significant wood accumulation could be detected due to the shorter flow path lengths.
Keywords: Engineering (miscellaneous); Ceramics and Composites